NUMERICAL SIMULATION OF TRANSIENT PROCESSES OF THE GROUNDWATER CONTAMINATION - Kalashnikov, I. V. (Science and Transport Progress, 2007)
A numerical model to calculate the process of ground waters protection from pollution with the use of neutralizator has been proposed. The model is based on the 2-D equations of filtration and admixture transfer. Results of numerical experiment are presented.